2020
DOI: 10.3390/microorganisms8071091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plasma-Activated Water on Skin Wound Healing in Mice

Abstract: Cold atmospheric plasma (CAP) has been widely used in biomedicine during the last two decades. While direct plasma treatment has been reported to promote wound healing, its application can be uneven and inconvenient. In this study, we first activated water with a portable dielectric barrier discharge plasma device and evaluated the inactivation effect of plasma-activated water (PAW) on several kinds of bacteria that commonly infect wounds. The results show that PAW can effectively inactivate these bacteria. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…In recent years, plasma-activated water (PAW) has gained prominence due to its application in medicine [1][2][3], mainly due to the effects of inactivation in microbial species caused basically by the stimulation of high biochemical and biological activities that alter the properties of water due to its exposure to plasma [4][5][6][7][8]. This plasma water activation technique is inexpensive and environmentally friendly since it is free of chemicals [9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, plasma-activated water (PAW) has gained prominence due to its application in medicine [1][2][3], mainly due to the effects of inactivation in microbial species caused basically by the stimulation of high biochemical and biological activities that alter the properties of water due to its exposure to plasma [4][5][6][7][8]. This plasma water activation technique is inexpensive and environmentally friendly since it is free of chemicals [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the murine model, the effect of PAS was complicated due to the complex biological systems. At present, studies on the application of plasma-activated liquid on infectious disease are focused on the treatment of wound infections, however, the injection of plasma-activated liquid for the treatment of internal infection has not been reported [ 60 , 61 ]. Several previous studies have demonstrated that plasma-activated medium produced by the dielectric barrier discharge device with the working gas of oxygen and air could induce the death of immunogenic cells by activating the innate immune system [ 32 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PAW equipment used here is a portable plasma equipment, so the equipment can be brought to the use site to prepare the required PAW to reduce the attenuation of active particles in the PAW. Our previous research has proven that PAW can effectively inactivate and reduce the bacterial load of common bacteria in wound infections, thereby promoting wound healing [34]. In order to further illustrate the effect of PAW on wound healing, we have also tested the ROS and RNS that play very important roles in biomedicine [37,38] in the PAW.…”
Section: Discussionmentioning
confidence: 99%
“…Timely treatment can also help avoid reductions in the biological effectivity of PAW due to time delays. In our previous research, we proved that the application of the PAW prepared with this portable device for 5 min can inactivate the most common bacteria present in wound infections [34]. In this paper, firstly, some discharge characteristics of the portable plasma equipment, and the concentrations of several important particles in the PAW, are tested.…”
Section: Introductionmentioning
confidence: 99%